Positive communication workshops: are they useful for treatment programmes for anorexia nervosa? - Tchanturia, Kate; Croft, Philippa; Holetic, Victoria; Webb, Jessica; Dapelo, Marcela Marin (Frontiers in Psychology, 2023)
Background Social isolation, loneliness and difficulties in relationships are often described as a core feature of eating disorders. Based on the experimental research, we have designed one-off workshops for patients in inpatients and day care services and evaluated its acceptability and effectiveness using feedback questionnaires. Methods This naturalistic project is an evaluation of multiple positive communication workshops. Forty-one participants completed workshop questionnaires, which were provided immediately at the beginning and end of the workshop, including feedback on these one-off groups. The workshops consisted of educational and experiential components. The questionnaire outcomes were evaluated by independent researchers. Results All participants were female adults with a mean age of 33 (12.2) and a diagnosis of Anorexia Nervosa (AN; either restrictive or binge-purge subtype). Post-workshop questionnaires showed large effect sizes in the improvement of understanding the importance and confidence in using positive communication strategies. Discussion Addressing social communication difficulties in eating disorder treatment programmes adds valuable dimensions to these symptom-based treatments in both inpatient settings and day services, and may provide broader benefits in overall social functioning in patients with AN. Conclusion Brief one-off workshops targeting social functioning for patients with eating disorders might be useful complementary input for treatment programmes.